EXAMINING THE SOCIO-ECONOMIC DYNAMICS: IMPACT OF HIGHWAY DEVELOPMENT ON COMMUNITIES IN HARYANA, INDIA - Rao, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study investigates the socio-economic dynamics resulting from highway development in Haryana, India, focusing on its impact on local communities. We explore both the positive and negative effects of improved transportation networks on socio-economic and spatial organization. A diverse demographic profile of respondents offers insights into how different factors influence perceptions of highway development. Positive impacts include enhanced standard of living, cultural exchange, entrepreneurship, and communication. However, concerns about cultural dilution, property price increases, and social conflicts highlight negative aspects. A comparative analysis of sector-involved and non-involved residents’ views reveals nuanced differences. Overall, this study underscores the need for balanced planning and mitigation strategies to ensure sustainable and inclusive development in regions experiencing highway expansion.